Mutation of CERKL, a Novel Human Ceramide Kinase Gene, Causes Autosomal Recessive Retinitis Pigmentosa (RP26) - Tuson, Miquel (The American Society of Human Genetics, 2004)
Retinitis pigmentosa (RP), the main cause of adult blindness, is a genetically heterogeneous disorder characterized by progressive loss of photoreceptors through apoptosis. Up to now, 39 genes and loci have been implicated in nonsyndromic RP, yet the genetic bases of >50% of the cases, particularly of the recessive forms, remain unknown. Previous linkage analysis in a Spanish consanguineous family allowed us to define a novel autosomal recessive RP (arRP) locus, RP26, within an 11-cM interval (17.4 Mb) on 2q31.2-q32.3. In the present study, we further refine the RP26 locus down to 2.5 Mb, by microsatellite and single-nucleotide polymorphism (SNP) homozygosity mapping. After unsuccessful mutational analysis of the nine genes initially reported in this region, a detailed gene search based on expressed-sequence-tag data was undertaken. We finally identified a novel gene encoding a ceramide kinase (CERKL), which encompassed 13 exons. All of the patients from the RP26 family bear a homozygous mutation in exon 5, which generates a premature termination codon. The same mutation was also characterized in another, unrelated, Spanish pedigree with arRP. Human CERKL is expressed in the retina, among other adult and fetal tissues. A more detailed analysis by in situ hybridization on adult murine retina sections shows expression of Cerkl in the ganglion cell layer. Ceramide kinases convert the sphingolipid metabolite ceramide into ceramide-1-phosphate, both key mediators of cellular apoptosis and survival. Ceramide metabolism plays an essential role in the viability of neuronal cells, the membranes of which are particularly rich in sphingolipids. Therefore, CERKL deficiency could shift the relative levels of the signaling sphingolipid metabolites and increase sensitivity of photoreceptor and other retinal cells to apoptotic stimuli. This is the first genetic report suggesting a direct link between retinal neurodegeneration in RP and sphingolipid-mediated apoptosis.